Pharmacognostic and Phytochemical Characterization of Colocasia esculenta var. antiquorum Corm (Araceae) and Preliminary Evaluation of Its Antimicrobial Activity - Sumiyati, Yati; Yesi Desmiaty; Gumilar Adhi Nugroho; Fauzia Noprima Okta (Journal of Natural Product for Degenerative Diseases, 2025)
Colocasia esculenta has been reported in reputable journals to exhibit various bioactivities, including antioxidant, anti-inflammatory, and antidiabetic properties. This study aimed to investigate the pharmacognostic characteristics and phytochemical profile of Colocasia esculenta var. antiquorum corm (Araceae). The corms were collected, authenticated, oven-dried, and subjected to preliminary pharmacognostic and phytochemical analyses. Pharmacognostic evaluations included organoleptic, microscopic, and physicochemical examinations. The dried corm powder was extracted with distilled water, followed by qualitative phytochemical screening. The extract was found to contain saponins, flavonoids, tannins, and triterpenoids. Antimicrobial activity was further evaluated against Staphylococcus aureus, Escherichia coli, and Candida albicans, which were selected as representative pathogenic microorganisms for Gram-positive bacteria, Gram-negative bacteria, and fungi, respectively. These microorganisms were chosen based on previous reports demonstrating that the ethanolic leaf extract of taro exhibited antifungal activity against Candida albicans and antibacterial activity against Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella, and Escherichia coli. However, no inhibitory effect was observed in this study. All analyses were performed in accordance with the guidelines of the Indonesian Herbal Pharmacopeia. The findings provide reference data for the pharmacognostic identification of Colocasia esculenta corm and highlight its phytochemical constituents. Further investigations on other biological activities are required to validate its therapeutic potential.